Trade of the Tricks : Inside the Magician's Craft - Jones, Graham M. (Book collections on Project MUSE., 2011)
From risque cabaret performances to engrossing after-hours shop talk, Trade of the Tricks offers an unprecedented look inside the secretive subculture of modern magicians. Entering the flourishing Paris magic scene as an apprentice, Graham M. Jones gives a firsthand account of how magicians learn to perform their astonishing deceptions. He follows the day-to-day lives of some of France's most renowned performers, revealing not only how secrets are created and shared, but also how they are stolen and destroyed. In a book brimming with humor and surprise, Jones shows how today's magicians marsha.